Optimalisasi Sistem Informasi Layanan Keuangan dengan Metode First Come First Served (FCFS) - Purwanto, Riyadi; Dwi Novia Prasetyanti; Cahya Vikasari; Rostika Listyaningrum (P3M Politeknik Negeri Cilacap, 2025)
One of the important things in financial management is financial services. Cilacap State Polytechnic (PNC) is a PTN as a Work Unit. Financial management at PNC refers to applicable government regulations, but financial service policies are the authority of the leadership as a strategy to create fast, effective, and accountable financial services. The budget usage policy stipulates that work units must propose budget usage based on the Fund Withdrawal Plan through a down payment form approved by the Financial Management Officer. The current problem is that down payment forms are often scattered or lost, so the response time for payments from finance is slow, and payment queues are often not in sequence. This results in activities being hampered. This research aims to create a prototype or development design for the Financial Services Information System at PNC. The FCFS method is used as a service scheduling algorithm based on arrival time to optimize financial services. In this way, the financial service process will be more organized, the response time for financial services will be faster, and the queue for service requests will be in line.